Drug Quality Control in Kenya: Observation in the Drug Analysis and Research Unit During the Period 2001-2005 (The East and Central African Journal of Pharmaceutical Sciences, 2018)
During the five-year period January 2001 to December 2005, the Drug Analysis and Research Unit received and analyzed 394 drug samples. Samples were received from regulatory authorities, local industry, non-governmental organizations, hospitals and private practitioners. The samples analyzed constituted 37.8 % locally manufactured and 62.2 % imported products. In contrast to previous years when failure rates of over 20 % were recorded, the overall rate of failure to comply with compendial quality specifications was 6.1 %, comprising of 8.7 % locally manufactured and 4.5 % imported drugs.
Keywords: Quality control; active pharmaceutical ingredient content; dissolution